Boron nitride nanoplatelets as reinforcement material for dental ceramics. Issue 6 (June 2020) - Lee, Bin; Kwon, Jae-Sung; Khalid, Muhammad Waqas; Kim, Kwang-Mahn; Kim, Joonhui; Lim, Kyoung Mook; Hong, Soon Hyung
Highlights: For the first time, boron nitride nanoplatelets (BNNPs) were introduced as a reinforcement material in dental materials. Homogenously dispersed BNNPs reinforced the zirconia composite, which exhibited enhanced mechanical properties. Cytotoxicity tests confirmed that the BNNPs do not have obvious toxicity. BNNPs inhibited the low temperature degradation of the zirconia matrix in humid environment. Abstract: Objective: The main goal of this research was to demonstrate the potential value of boron nitride nanoplatelets (BNNPs), which have excellent mechanical properties and biocompatibility, as a suitable reinforcement for dental materials. Methods: The BNNPs were prepared by exfoliating h-BN via high-energy ball-milling and dispersion on a zirconia matrix. Then the composite powder was consolidated using spark plasma sintering. Fracture toughness, flexural strength and wear resistance were the mechanical properties explored. Agar diffusion-based biocompatibility testing was carried out. Low temperature degradation tests were also performed in a steam environment in an autoclave. Results: The BNNPs dispersed zirconia exhibited improved strength (up to 27.3%), and fracture toughness was also increased (up to 37.5%) with the addition of 1–1.5 vol.% BNNPs. Tribological properties were also enhanced by the addition of BNNPs. The cytotoxicity tests confirmed that the BNNPs do not have obvious toxicity. The accelerated low-temperature degradation experiment revealed the barrier properties of the BNNPs, whose addition almost fully inhibited the degradation of the zirconia matrix in a humid environment. Significance: The main contribution of this study is the introduction of an advanced material, BNNP, which can be used as a biocompatible reinforcement for dental materials, resulting in enhanced mechanical properties of the system due to its unique structure and extraordinary properties.